The state and main directions in the development of earth’s interior resources - К. N. Trubetskoy (Известия высших учебных заведений: Геология и разведка)
Background. In order to achieve a high efficiency in the development of deep-seated deposits, mining sciences are required to optimize the parameters of mining operations, equipment and technology, to study and develop the principles of a rational combination of various resource-saving, low-waste and resource-reproducing technological processes, above all, providing the widespread use of automated planning systems and methods for managing the extraction of minerals.Aim. To analyse the state and main directions in the development of the Earth’s interior resources.Materials and methods. The research was carried out on the basis of a comprehensive analysis of scientific publications, reports and archive materials on the development of mineral resources.Results. A scheme describing the formation of a consolidated natural-technogenic massif in the Earth’s interior and a technological diagram of the movement of mineral-raw material flows are presented. A conclusion is made that it is expedient to create the technologies for the purposeful formation of deposits on the basis of the principle of geotechnological continuation of the formation of useful components by artificial methods using natural forces to transform deposits to a state that is maximally acceptable for subsequent development. Such technologies should provide the creation of conditions in the massif for the spatial separation of useful components, changes in the physical properties of rocks, the conditions of occurrence of minerals and, on this basis, increasing the efficiency of traditional and new ways of developing deposits.Conclusion. The use of these technologies will allow the resource base to be expanded by increasing the concentration of useful components in the Earth’s interior and involving poor deposits and ore occurrences in the development; to increase the value of deposits due to associated components obtained in the processes of material transformation of ores; to reduce the depth of mining operations due to the formation of technogenic deposits on geochemical barriers near the Earth’s surface; to reduce the development time of deposits; and to reduce the technogenic load on the environment. The creation of such technologies will require a deep integration of the efforts of geologists, geochemists, geophysicists, ecologists and miners.